An effective method of UV-oxidation of dissolved organic carbon in natural waters for radiocarbon analysis by accelerator mass spectrometry - Xue Yuejun; Ge Tiantian; Wang Xuchen (JOURNAL OF OCEAN UNIVERSITY OF CHINA, 2015)
Radiocarbon (C-14) measurement of dissolved organic carbon (DOC) is a very powerful tool to study the sources, transformation and cycling of carbon in the ocean. The technique, however, remains great challenges for complete and successful oxidation of sufficient DOC with low blanks for high precision carbon isotopic ratio analysis, largely due to the overwhelming proportion of salts and low DOC concentrations in the ocean. In this paper, we report an effective UV-Oxidation method for oxidizing DOC in natural waters for radiocarbon analysis by accelerator mass spectrometry (AMS). The UV-oxidation system and method show 95%+/- 4% oxidation efficiency and high reproducibility for DOC in both river and seawater samples. The blanks associated with the method was also low (about 3 A mu g C) that is critical for C-14 analysis. As a great advantage of the method, multiple water samples can be oxidized at the same time so it reduces the sample processing time substantially compared with other UV-oxidation method currently being used in other laboratories. We have used the system and method for C-14 studies of DOC in rivers, estuaries, and oceanic environments and have received promise results.
Keywords: AMS; dissolved organic carbon; natural waters; radiocarbon; UV-oxidation